2015
DOI: 10.1186/s12906-015-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic effects of phenolic compounds on pancreatic stellate cells

Abstract: BackgroundPancreatic fibrosis is a prominent histopathological characteristic of chronic pancreatitis and plausibly a dynamic process of transition to the development of pancreatic ductal adenocarcinoma. Conversely, the activation of pancreatic stellate cells (PSCs) has been recently suggested as the key initiating step in pancreatic fibrosis. As natural polyphenols had been largely applied in complementary therapies in the past decade, in this study, we aimed to investigate which groups of phenolic compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Even so, it remains challenging to model alcohol‐related fibrosis in rodent models and there is a need to more fully determine the exact individual and collective roles of EtOH, its metabolic products, or endotoxin on the initiation or aggravation of pancreatic fibrosis. Col1 has been confirmed as the major component of extracellular matrix in the pancreas of human ACP and animal models of alcohol‐related pancreatitis (Lin et al., ; Masamune et al., ). Although a little aniline blue‐stained collagen was detected in periacinar and perilobular regions (data not shown) where PSCs could be detected, the vast majority of Col1 was only found in PSCs and 3.1‐fold increase in Col1A1 protein was detected in the pancreas of 10‐week EtOH rats, indicating that Col1 is a more sensitive and specific marker for assessing pancreatic fibrogenesis in 10‐week EtOH rat model.…”
Section: Discussionmentioning
confidence: 97%
“…Even so, it remains challenging to model alcohol‐related fibrosis in rodent models and there is a need to more fully determine the exact individual and collective roles of EtOH, its metabolic products, or endotoxin on the initiation or aggravation of pancreatic fibrosis. Col1 has been confirmed as the major component of extracellular matrix in the pancreas of human ACP and animal models of alcohol‐related pancreatitis (Lin et al., ; Masamune et al., ). Although a little aniline blue‐stained collagen was detected in periacinar and perilobular regions (data not shown) where PSCs could be detected, the vast majority of Col1 was only found in PSCs and 3.1‐fold increase in Col1A1 protein was detected in the pancreas of 10‐week EtOH rats, indicating that Col1 is a more sensitive and specific marker for assessing pancreatic fibrogenesis in 10‐week EtOH rat model.…”
Section: Discussionmentioning
confidence: 97%
“…Tsang et al . and Lin et al . demonstrated that resveratrol can suppress the activation of PSCs, and the suppressive effects are associated with a decrease in NF‐κB activation and Akt phosphorylation.…”
Section: The Role Of Resveratrol In the Tumor Microenvironmentmentioning
confidence: 99%
“…By producing its characteristic protective mechanisms, resveratrol also exhibited beneficial effects in liver injury associated with severe AP (Sha et al , ,b). Apart from the protection against AP, resveratrol also produced antifibrotic effects on LTC‐14 PSCs, suggesting its use in chronic pancreatic conditions (Lin et al , ).…”
Section: Herbal Remedies Used For Treating Pancreatitismentioning
confidence: 99%
“…Curcumin also protected the PSCs (LTC‐14) from fibrotic effects by inhibiting the mRNA expression of alpha‐smooth muscle actin, type I collagen, etc. (Lin et al , ). By checking the TLR‐4/NF‐κB signaling pathway, curcumin produced protective effects in severe AP (Zhong, ).…”
Section: Herbal Remedies Used For Treating Pancreatitismentioning
confidence: 99%